“Safety Is Elusive:” A Critical Discourses Analysis of Newspapers’ Reporting of Domestic Violence During the Coronavirus Pandemic - Storer, Heather L. (Violence against women, 2024)
The COVID-19 pandemic exacerbated incidences of domestic violence (DV). The framing of DV within media sources contributes to the public's understanding of DV. Using critical discourse analysis (CDA), this paper explores representations of safety within newspapers’ reporting of DV during the pandemic. The sample included newspaper articles (n = 31) from U.S. newspapers. The analysis involved multiple rounds of coding and employing “structured questions.” These articles depicted limited courses of action for DV survivors and represented safety as unattainable. Safety was constructed in four ways: homes are unsafe, social services are overburdened, government failures, and the elusiveness of safety. These discursive formations provide insight regarding “idealized” social responses to DV.